Kontribusi Harga Komoditi Pertanian Terhadap Inflasi di Kota Manado - Amelia E. Rotulung; Charles R. Ngangi; Esry O.H. Laoh; Melisa L.G. Tarore (Universitas Sam Ratulangi, 2015)
ABSTRACTThe purpose of this research is to show whether or not the contribution of agricultural commodity prices to inflation in the city of Manado .The experiment is conducted from September 2013 to February 2014. This research uses secondary data obtained from the Central Bureau of Statistics of North Sulawesi Province . The data is taken in the form of a time series of the year 2004-2013 from the Central Bureau of Statistics of North Sulawesi Province . Data is analyzed by multiple linear regression using SPSS Statistics version 20 .The results showed that the coefficient of determination ( R2 ) of the regression 0,860 or 86 percent and adjusted coefficient of determination ( Radj ) is 0.684 or 68.4 percent . The coefficient of determination of 86 percent means that the inflation of grains , vegetables inflation , inflation nuts , fruits inflation and inflation spices can explain inflation in the Manado, at 86 percent and the rest of 14 percent is explained by the others variables that are not included in the model . The highest contribution is other commodity of Nuts commodity is 0.289 percent and the lowest commodity is -0.438 percent .Keywords : Contribution, Inflation, Commodity of Agriculture